Gingivitis in calves: longitudinal hematological and metabolic profiles-and salivary buffering capacity in animals treated with virginiamycin - Vaccari, Juliana [UNESP]; Ramos, Thamiris Naiasha Minari [UNESP]; Júnior, Elerson Gaetti-Jardim [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Borsanelli, Ana Carolina; Saraiva, Júlia Rebecca [UNESP]; de Souza, Natália Cristina [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Schweitzer, Christiane Marie [UNESP]; Dos Santos Dutra, Iveraldo [UNESP] (FapUNIFESP (SciELO), 2023)
Gingivitis is an infectious inflammatory process that generates local and systemic conditions, compromising the masticatory capacity of animals. Virginiamycin controls and prevents gingivitis and necrotizing gingivitis in cattle. However, the interaction and effect with different sera and salivary elements remain unknown. The present 6-month longitudinal study evaluated the hematological, metabolic, and salivary buffering capacity profiles of calves with gingivitis treated with virginiamycin. Ten calves were divided into two groups: control and virginiamycin (n = 5 each). Calves in the virginiamycin group had a lower occurrence of gingivitis (P < 0.01, Student’s t-test). The animals that developed gingivitis in both experimental groups had higher salivary levels of alkaline phosphatase (P = 0.01915) and lower serum levels of albumin (P = 0.0028). Additionally, animals receiving virginiamycin had higher serum levels of magnesium (P = 0.008), albumin (P = 0.0008), urea (P = 0.008), alkaline phosphatase (P = 0.008), total proteins (P = 0.008), and plasma protein (P = 0.018). Salivary buffering capacity was negatively correlated with salivary variables such as calcium, magnesium, albumin, total protein, and aspartate aminotransferase and serum variables such as albumin and aspartate aminotransferase. Results of the present study suggested that the occurrence of periodontopathies in episodes is reflected in the local and systemic alterations in animals. In this context, clinical periodontal monitoring also showed the benefits of virginiamycin supplementation on gingival conditions and systemic health markers, in addition to controlling the two precursor forms of periodontitis.
Gengivites em bezerros: perfis longitudinais hematológicos, metabólicos e capacidade tamponante salivar em animais tratados com virginiamicina
Keywords: cattle; gingivitis; necrotizing gingivitis; salivary biochemistry; serum biochemistry; virginiamycin